Selective distribution of protein kinase A regulatory subunit RIIα in rodent gliomas - Mucignat-Caretta, Carla (Duke University Press, 2008)
Differential diagnosis of brain tumor types is mainly based on cell morphology and could benefit from additional markers. The cAMP second-messenger system is involved in regulating cell proliferation and differentiation and is conceivably modulated during cancer transformation. The cAMP second-messenger system mainly activates protein kinases, which are in part docked to cytoskeleton, membranes, or organelles by anchoring proteins, forming protein aggregates that are detergent insoluble and not freely diffusible and that are characteristic for each cell type. The intracellular distribution of the detergent-insoluble regulatory subunits (R) of the cAMP-dependent protein kinase has been examined in mouse and rat glioma cells both in vitro and in vivo by immunohistochemistry. In normal rodent brains, the RIIα regulatory subunit is detergent insoluble only in ependymal cells, while in the rest of the brain it is present in soluble form. Immunohistochemistry shows that in both mouse and rat glioma cell lines, RIIα is mainly detergent insoluble. RIIα is localized close to the nucleus, associated with smooth vesicles in the trans-Golgi network area. Both paclitaxel and vinblastine cause a redistribution of RIIα within the cell. Under conditions that increased intracellular cAMP, apoptosis of glioma cells was observed, and it was accompanied by RIIα redistribution. Also in vivo, detergent-insoluble RIIα can be observed in mouse and rat gliomas, where it delineates the border between normal brain tissue and glioma. Therefore, intracellular distribution of detergent-insoluble RIIα can assist in detecting tumor cells within the brain, thus making the histologic diagnosis of brain tumors more accurate, and may represent an additional target for therapy.